2019
DOI: 10.1111/sji.12816
|View full text |Cite
|
Sign up to set email alerts
|

Local IL‐10 level as a predictive factor in generalized aggressive periodontitis treatment response

Abstract: Generalized aggressive periodontitis (GAgP) presents a reduced response to non‐surgical therapy. However, it is not clear if the initial clinical, microbiological or immunological characteristics are impacting the worse response to treatment. This study aimed to identify the predictive value of clinical, microbiological and immunological patterns on the clinical response to therapy in GAgP patients. Twenty‐four GAgP patients were selected, and gingival crevicular fluid (GCF) and subgingival biofilm were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…Moreover, IL-10 has a key function in the osteoclastic bone resorption and the regulation of osteoblastic bone formation [57]. Taiete et al (2019) demonstrated that in generalized aggressive periodontitis patients treated with scaling and root planning, a higher IL-10 concentration at baseline was associated with a higher reduction in probing pocket depth at 6 months [58]. One recent study has demonstrated, in an animal model, which IL-10 can modulate local host immune responses and prevent inflammatory damage of alveolar bone by reducing pro-inflammatory cytokine expression and decreasing local proliferation of Th17 cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-10 has a key function in the osteoclastic bone resorption and the regulation of osteoblastic bone formation [57]. Taiete et al (2019) demonstrated that in generalized aggressive periodontitis patients treated with scaling and root planning, a higher IL-10 concentration at baseline was associated with a higher reduction in probing pocket depth at 6 months [58]. One recent study has demonstrated, in an animal model, which IL-10 can modulate local host immune responses and prevent inflammatory damage of alveolar bone by reducing pro-inflammatory cytokine expression and decreasing local proliferation of Th17 cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…This is important when some microbiological assays have shown a more specific microbial community in Perio4C, 33,34 along with altered cytokines in gingival fluid, as IL-10. 35 IL-10 is a cytokine that can be produced by multiple immune cell types, including the T regulatory (Treg) cells, as is a more relevant representant for the Treg response. These cells are known for producing cytokines that suppress the inflammatory response against specific pathogens, restricting the host tissue damage during chronic infection.…”
Section: Rs6667202 Modulates Hgfs Il-10 Response After Stimulationmentioning
confidence: 99%
“…12 These include the pro-inflammatory cytokines IL-1β, 13,14 TNFα, 13,15 IL-8, 15,16 and IL-6 16 and the anti-inflammatory cytokine IL-10. [17][18][19] These biomarkers initiate the gingival inflammatory response to microbial plaque, mobilize immune cells to the gingival tissues, and advance the inflammatory front closer to the alveolar bone leading to periodontal tissue damage. 20 Vegetarian dietary patterns have been associated with lower levels of blood inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…Plaque‐related inflammatory periodontal disease is associated with increased levels of several inflammatory biomarkers in the gingival tissues 12 . These include the pro‐inflammatory cytokines IL‐1β, 13,14 TNF‐α, 13,15 IL‐8, 15,16 and IL‐6 16 and the anti‐inflammatory cytokine IL‐10 17–19 . These biomarkers initiate the gingival inflammatory response to microbial plaque, mobilize immune cells to the gingival tissues, and advance the inflammatory front closer to the alveolar bone leading to periodontal tissue damage 20 …”
Section: Introductionmentioning
confidence: 99%